2021
DOI: 10.1016/j.heliyon.2021.e07950
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of data collection, analysis, and reporting adopted for water quality assessment: A case of Nigeria water quality research

Abstract: The appropriate acquisition and processing of water quality data are crucial for water resource management. As such, published articles on water quality monitoring and assessment are meant to convey essential and reliable information to water quality experts, decision-makers, researchers, students, and the public. The implication is that such information must emanate from data obtained and analysed in an up-to-date, scientifically sound manner. Thus, inappropriate data analysis and reporting techniques could y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 125 publications
0
0
0
Order By: Relevance
“…Helsel et al, [25] and Ewuzie et al, [26] provided a description of the sufficiency, trustworthiness, and representation of environmental data. The peak area for each energy in the spectrum of gamma spectroscopy was used to compute the activity concentrations in each sample using equation 11 [27].…”
Section: Activity Concentrations Of Soil Samplesmentioning
confidence: 99%
“…Helsel et al, [25] and Ewuzie et al, [26] provided a description of the sufficiency, trustworthiness, and representation of environmental data. The peak area for each energy in the spectrum of gamma spectroscopy was used to compute the activity concentrations in each sample using equation 11 [27].…”
Section: Activity Concentrations Of Soil Samplesmentioning
confidence: 99%
“…Mustapha (2008) suggested that changes in these characteristics provide valuable information about water quality and its impact on the functionality and biodiversity of an aquatic ecosystem. Ewuzie et al (2021) emphasized that the primary sources of water in the South-South region of Nigeria are boreholes, shallow wells, creeks, and rivers, and studies have been conducted on their water qualities (Owoyemi et al, 2019;Ihunwo et al, 2020;Ocheli et al, 2020;Owamah, 2020). Research in the South-West focused on rivers, lagoons, ground waters, lakes, and streams (Odukoya et al, 2017;Ezemonye et al, 2019;Ebele et al, 2020;Gbadebo, 2020;Ogunbanwo et al, 2020), while studies in the South-East region evaluated the physicochemical factors of ground waters such as dug-wells, boreholes, springs, streams, and lakes, with few studies on rivers (Chukwuka et al, 2019;Egbueri et al, 2019;Alum & Okoye, 2020;Ewuzie et al, 2020;Naganje et al, 2020).…”
Section: Introductionmentioning
confidence: 99%